Tinjauan Hukum Ekonomi Syariah terhadap Jual Beli Bawang Merah dengan Sistem Panjar - Ulumuddin, Imam Khoirul; Handayani, Zidni Ilma; Nurasikin , Akhmad; Handayani, Tri (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2024)
Selling and buying shallots with a panjar system is to pay in advance the agreed down payment  and the lack of payment will be paid after the shallots are harvested. In the payment, it has applied a down payment, but it is not uncommon for the sale and purchase of shallots to experience cancellation, the cancellation can be from the seller or buyer. The purpose of this study was to determine the practice of buying and selling shallots with a panjar system in Kluwan Village, Penawangan District, Grobogan Regency and Sharia Economic Law Review of the practice. This study is field research with a qualitative approach. While data collection through observation, interviews, and documentation. The result of this study is that the practice of buying and selling shallots with a panjar system in Kluwan Village, Penawangan District, Grobogan Regency starts with bargaining between sellers and buyers, until an agreement and agreement occurs. The review of sharia economic law on the practice of buying and selling shallots in Kluwan Village, Penawangan District, Grobogan Regency uses a panjar system in accordance with the terms of the harmony of the sale and purchase contract, and the absence of gharar elements because there is already an agreement or agreement between the seller and the buyer.